2019
DOI: 10.21831/cp.v38i1.22283
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of “Pik-R” Program as an Extracurricular for High/Vocational School Students in Preventing Negative Behaviors of Adolescents

Abstract: PIK-R (Pusat Informasi Konseling Remaja) as one of the programs for adolescents is expected to be able to contribute positively in developing positive behavior and suppress the potential for negative adolescent behavior. This study aims to analyze the positive and negative behavior of high/vocational school students and their relation to knowledge, participation, and effectiveness of the PIK-R program at school. This study used a cross sectional study design involving 687 students in selected public and privat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…School counsellors may help with suitable effective program that helps these students not to be involved in misbehaviour. This has been proven by Hastuti et al (2019) showing that school students who involve in school program are found less to be involved in any misbehaviour at school.…”
Section: Discussionmentioning
confidence: 96%
“…School counsellors may help with suitable effective program that helps these students not to be involved in misbehaviour. This has been proven by Hastuti et al (2019) showing that school students who involve in school program are found less to be involved in any misbehaviour at school.…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, community involvement and support, particularly from religious leaders, significantly help promote healthy behavior (Wati et al, 2017 ; Winarni & Martiningsih, 2019 ). Active support from health services, schools, extracurricular coaches, and the government is critical to the GenRe program’s efforts to decrease negative adolescent behaviors, particularly pornographic exposure, addiction to risky sexual behavior, online gaming, and smoking (Hastuti, 2019 ; Sari & Indrawadi, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, students who participated in the PIK-R program showed significantly lower negative behaviors. 20 Therefore, the implementation of PIK-R should be more encouraged and supported as an effective way to improve the knowledge and behavior of adolescents.…”
Section: Discussionmentioning
confidence: 99%